Validation case studies of a numerical approach towards optimization of novel fuselage geometries - Odendaal, Diwan U.; Smith, Lelanie; Craig, Ken; Mutangara, Ngonidzashe; Sanders, Drewan S. (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Optimization studies for improved fuselage designs primarily focus on drag reduction. However, when considering an alternative configuration where the stability requirements are assumed to be fulfilled by the main wing, eliminating the need for a tailplane, the fuselage design requirements are reconsidered. This work considers not only the reduction of drag but ensuring a component of lift as well as considering energy recovery potential for propulsion integration. The numerical modelling approach (turbulence model selection, optimization strategy and application of the Power Balance Method) is evaluated through a series of validation cases to determine a level of robustness and certainty. Three cases studies are completed: a 2D, compressible transonic RAE2282 airfoil, a 3D, incompressible low-drag body F-57 and a 3D, compressible body MBB3. The final approach includes a polyhedral mesh and SST k-ω turbulence model combined with multi-objective tradeoff optimization. Application of the Power Balance Method was validated within 1% for incompressible cases, however for the compressible cases the drag coefficient showed increasing deviation (1.3%) due to residual dissipative quantities.